Aspectos epidemiológicos da infecção por cryptosporidium em equinos - Inácio, Sandra Valéria [UNESP]; De Brito, Roberta Lomonte Lemos [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2013)
Inquiries about cryptossporidiosis are essential because its zoonotic potential and pathogenicity in pets and production animals. The horse can be involved in the transmission of the infection by Cryptosporidium and can have an epidemiological role in this disease. The great possibility of adquiring this protozoan, justify the importance of attempting against for the occurrence of this illness. The aim of this article was to demonstrated through literature revision, some epidemiological aspects of the cryptosporidiosis in the equine specie.
Epidemiological aspects of Cryptosporidium infection in horses
Keywords: Coccidia; Cryptosporidium; Equine